Disease: A Major Stumbling Block in the Growth of Aquaculture - Dheeraj S. B; Puneeth T. G; Amogha K. R (International Journal of Marine Life, 2024)
Aquaculture plays a crucial role in ensuring food security, fostering economic development, and providing recreational opportunities worldwide. However, the intensification of aquaculture practices has led to a surge in environmental challenges, including water pollution, soil acidification, eutrophication, chemical contamination, and the spread of diseases. Among these, diseases caused by bacteria, viruses, fungi, and parasites pose significant threats to the sustainability of global aquaculture. Despite the implementation of various diagnostic methods and control measures, the success rate in managing these diseases remains low due to asymptomatic infections and the lack of effective therapeutics. Viral diseases, in particular, present formidable challenges due to their rapid spread, high morbidity rates, and limited understanding of aquatic animal immune responses. Current strategies such as selective breeding for resistance and vaccination have shown limited success in controlling viral outbreaks. Bacterial infections also pose significant obstacles to aquaculture, with common pathogens such as Aeromonas spp. and Vibrio spp. causing widespread diseases. Parasitic infections, although less common, can have devastating ecological and economic consequences if left untreated. In the face of these challenges, there is a growing need for sustainable control measures to mitigate the risks associated with disease outbreaks. Vaccination, probiotics, and biotechnological advances such as gene therapy and genetically modified species offer promising avenues for disease prevention and management. Additionally, integrating immunomodulators, metal nanoparticles, herbal products, and biofilm vaccination into aquaculture practices shows potential for enhancing disease resistance. Overall, adopting sound management practices and strict biosecurity measures is essential for minimizing the impact of pathogens on fish and aquaculture systems, thereby ensuring the long-term sustainability of this vital industry.
Keywords: Bacterial Diseases; Fungal and Parasitic Diseases; Viral Diseases; aquaculture